2021
DOI: 10.1111/jfs.12942
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of human gut lactic acid bacteria against aflatoxigenic Aspergillus flavus MTCC 2798 and their potential application as food biopreservative

Abstract: With the enhanced use of chemical preservatives and the survival of foodborne pathogens, lactic acid bacteria and its metabolic product have received increased attention as a potential food preservative. Even though the antibacterial property of lactic acid bacteria is well known, its antifungal property and application in food preservation have not been widely exploited. Considering these facts, this study was conducted to investigate the antifungal properties of three human gut lactic acid bacterial isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Similar results were reported by Parappilly et al. [64] , who revealed that all three methanolic extracts of the isolates ( L. plantarum AL1, L. fermentum AL2, and Weissella confusa AL3) showed very high inhibitory activity towards aflatoxigenic A. flavus MTCC 2798. The antifungal action of L. rhamnosus ethyl acetate extract No.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were reported by Parappilly et al. [64] , who revealed that all three methanolic extracts of the isolates ( L. plantarum AL1, L. fermentum AL2, and Weissella confusa AL3) showed very high inhibitory activity towards aflatoxigenic A. flavus MTCC 2798. The antifungal action of L. rhamnosus ethyl acetate extract No.…”
Section: Discussionsupporting
confidence: 89%
“…55,56 Other bioactive compounds of T. asperellum extracts butylated hydroxytoluene, cyclo(L-prolyl-Lvaline), cyclo(leucyloprolyl), 9-octadecenoic acid, and hydroquinone were mentioned to exert antifungal activity against wide range of fungal plant pathogens and mycotoxigenic fungi in previous studies. 57 Nofal et al 58 reported that globulol exhibited high antifungal activity against F. graminearum, A. solani and R. solani.…”
Section: Discussionmentioning
confidence: 99%
“…Anju et al [ 25 ] had reported the identification of BEHP as one of the metabolites produced by a nematode symbiotic bacterium associated with a novel entomopathogenic nematode Rhabditis species. Previously, authors have reported that L. plantarum also produce such types of metabolites, e.g., diisooctyl phthalate [ 39 ]. However, no specific results have been reported on the isolation of Bis-(2-ethylhexyl) phthalate (BEHP); hence, the current report describes the isolation and characterization of BEHP from L. plantarum BCH-1 for the first time.…”
Section: Discussionmentioning
confidence: 99%